Clinical Utility of NT-proBNP in the Diagnosis and Management of Heart Failure: A Comprehensive Review - Abhinav Prithvi Venkata Sesha Kanigicherla; Unnagiri Adinarayana; Vasamsetti Kumar Swamy; Gorle Sujatha; Bura Ramya Sri; Setti Gayathri Devi (International Journal of Recent Advances in Multidisciplinary Topics, 2026)
Background: Heart failure (HF) is a major global public health problem associated with high morbidity, mortality, and healthcare costs. Early diagnosis and timely management are essential to improve clinical outcomes. N-terminal pro-B-type natriuretic peptide (NT-proBNP), a biomarker released in response to myocardial wall stress, has become an important tool for the diagnosis, prognosis, and therapeutic monitoring of patients with heart failure. Objective: This review aims to summarize the current evidence regarding the clinical utility of NT-proBNP in the diagnosis, risk stratification, prognosis, and management of heart failure, while highlighting factors that influence its interpretation and emerging clinical applications. Methods: A comprehensive literature review was conducted using peer-reviewed articles, clinical guidelines, systematic reviews, and meta-analyses published in major electronic databases, including PubMed, Scopus, and Google Scholar. Relevant studies addressing the diagnostic, prognostic, and therapeutic applications of NT-proBNP in heart failure were reviewed and critically analyzed. Results: NT-proBNP is a highly sensitive biomarker for the diagnosis of both acute and chronic heart failure and provides significant prognostic information regarding disease severity, hospitalization, and mortality. Its measurement aids in differentiating cardiac from non-cardiac causes of dyspnea, assessing treatment response, and identifying patients at increased risk of adverse cardiovascular outcomes. However, NT-proBNP concentrations are influenced by factors such as age, renal dysfunction, obesity, atrial fibrillation, and other comorbidities, which should be considered during clinical interpretation. Conclusion: NT-proBNP plays a pivotal role in the contemporary management of heart failure by facilitating early diagnosis, prognostic assessment, and therapeutic decision-making. When interpreted in conjunction with clinical findings and imaging modalities, it significantly enhances patient care. Continued research into biomarker-guided management strategies and integration with novel diagnostic approaches may further improve outcomes in patients with heart failure.